Dynamic and Static Amplitude of Low-Frequency Fluctuation Is a Potential Biomarker for Predicting Prognosis of Degenerative Cervical Myelopathy Patients: A Preliminary Resting-State fMRI Study - Fan, Ningjian; Zhao, Bing; Liu, LiYun; Yang, WeiZhen; Chen, Xian; Lu, ZhanBin (Frontiers in Neurology, 2022)
Abstract Objective: The aim of this study was to explore the clinical value of static amplitude of low frequency fluctuation (sALFF) and dynamic amplitude of low frequency fluctuation (dALFF) in identification of brain functional alterations in degenerative cervical myelopathy (DCM) patients. Methods: Voxel-wise sALFF and dALFF of 47 DCM patients and 44 healthy controls were calculated using resting-state fMRI data; and intergroup comparison was performed. The mean of sALFF or dALFF data were extracted within the resultant clusters and the correlation analysis of these data with the clinical measures was performed. Furthermore, whole-brain wise and region wise multi-variate pattern analyses were performed to classify DCM patients and healthy controls. sALFF and dALFF were used to predict the prognosis of DCM patients . Results: The findings showed that (1) DCM patients exhibited higher sALFF within left thalamus and putamen compared with that of healthy controls. DCM patients also exhibited lower dALFF within bilateral postcentral gyrus compared with the healthy controls; (2) No significant correlations were observed between brain alterations and clinical measures through univariate correlation analysis; (3) sALFF (91%) and dALFF (95%) exhibited high accuracy in classifying DCM patients and healthy controls; (4) Region-wise MVPA further revealed brain regions in which functional patterns were associated with prognosis in DCM patients. These regions were mainly located at the frontal lobe and temporal lobe. Conclusion: In summary, sALFF and dALFF can be used to accurately reveal brain functional alterations in DCM patients. Furthermore, multi-variate approach is a more sensitive method in exploring neuro-pathology and establishing a prognostic biomarker for DCM compared with the conventional univariate method.